Prognostic implication of heterogeneity and trajectory progression induced by enzalutamide in prostate cancer - Feng, Yuanfa; Deng, Yulin; Tang, Zhenfeng; Cai, Shanghua; Li, Jinchuang; Liu, Ren; Wan, Jiaming; He, Huichan; Zeng, Guohua; Ye, Jianheng; Han, Zhaodong; Zhong, Weide (Frontiers in Endocrinology, 2023)
Background: Enzalutamide, as a second-generation endocrine therapy drug for prostate cancer (PCa) is prominent representative among synthetic AR antagonists. Currently, there is lack of enzalutamide-induced signature for predicting progression and relapse-free survival (RFS) in PCa. Methods: Enzalutamide-induced candidate markers were derived from single-cell RNA-sequencing analysis integrating three enzalutamide-stimulated models (0-hour, 48-hour, 168-hour enzalutamide stimulation). Enzalutamide-induced signature (ENZ-sig) was constructed based on candidate genes that were associated with RFS in TCGA leveraging Least absolute shrinkage and selection operator method. The ENZ-sig was further validated in GSE70768, GSE94767, E-MTAB-6128, DFKZ, GSE21034, and GSE70769. Biological enrichment analysis was used to discover the underlying mechanism between high ENZ-sig and low ENZ-sig in single-cell RNA sequencing and bulk RNA-sequencing. Results: We identified a heterogenous subgroup that induced by enzalutamide stimulation and found 53 enzalutamide-induced candidate markers that related to trajectory progression and enzalutamide-stimulated. The candidate genes were further narrowed down into 10 genes that related to RFS in PCa. A ten-gene prognostic model (ENZ-sig), including IFRD1, COL5A2, TUBA1A, CFAP69, TMEM388, ACPP, MANEA, FOSB, SH3BGRL and ST7 was constructed for the prediction of RFS in PCa. The effective and robust predictability of ENZ-sig was verified in six independent datasets. Biological enrichment analysis revealed that differentially expressed genes in high ENZ-sig were more activated in cell cycle related pathway. High levels of ENZ-sig displayed more sensitive with cell-cycle-targeted drugs (MK-1775, AZD7762, MK-8776) than those with low ENZ-sig patients in PCa. Conclusions: Our results provided evidence and insight on the potential utility of ENZ-sig in PCa prognosis and combination-therapy strategy of enzalutamide and cell-cycle-targeted compounds in treating PCa.